Dissolution in a variably confined carbonate platform: effects of allogenic runoff, hydraulic damming of groundwater inputs, and surface–groundwater exchange at the basin scale. Issue 14 (26th March 2013) - Gulley, J.; Martin, J.; Spellman, P.; Moore, P.; Screaton, E.
ABSTRACT: In variably confined carbonate platforms, impermeable confining units collect rainfall over large areas and deliver runoff to rivers or conduits in unconfined portions of platforms. Runoff can increase river stage or conduit heads in unconfined portions of platforms faster than local infiltration of rainfall can increase groundwater heads, causing hydraulic gradients between rivers, conduits and the aquifer to reverse. Gradient reversals cause flood waters to flow from rivers and conduits into the aquifer where they can dissolve limestone. Previous work on impacts of gradient reversals on dissolution has primarily emphasized individual caves and little research has been conducted at basin scales. To address this gap in knowledge, we used legacy data to assess how a gradient of aquifer confinement across the Suwannee River Basin, north‐central Florida affected locations, magnitudes and processes of dissolution during 2005–2007, a period with extreme ranges of discharge. During intense rain events, runoff from the confining unit increased river stage above groundwater heads in unconfined portions of the platform, hydraulically damming inputs of groundwater along a 200 km reach of river. Hydraulic damming allowed allogenic runoff with SICAL  < −4 to fill the entire river channel and flow into the aquifer via reversing springs. Storage of runoff in the aquifer decreased peak river discharges downstream and contributed to dissolution within the aquifer. Temporary storage of allogenic runoff in karst aquifers represents hyporheic exchange at a scale that is larger than found in streams flowing over non‐karst aquifers because conduits in karst aquifers extend the area available for exchange beyond river beds deep into aquifers. Post‐depositional porosity in variably confined carbonate platforms should thus be enhanced along rivers that originate on confining units. This distribution should be considered in models of porosity distribution used to manage water and hydrocarbon resources in carbonate rocks. Copyright © 2013 John Wiley & Sons, Ltd.